2017
DOI: 10.2147/amep.s124004
|View full text |Cite
|
Sign up to set email alerts
|

Faculty development for the evaluation system: a dual agenda

Abstract: Faculty development for the evaluation process serves two distinct goals. The first goal is to improve the quality of the evaluations submitted by the faculty. Providing an accurate assessment of a learner’s capabilities is a skill and, similar to other skills, can be developed with training. Frame-of-reference training serves to calibrate the faculty’s standard of performance and build a uniform language of the evaluation. Second, areas for faculty professional growth can be identified from data generated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thus, the Milestones 2.0 must be clearly articulated and reliably understood by faculty 8 . An evidence‐based methodology to foster the shared mental model, ensure high‐quality evaluations by faculty, and develop means to identify areas for improvement using learner feedback is suggested 9 . Three significant changes made to the original Milestones include updates to the content, revision of the rating system, and creation of a Supplemental Guide.…”
Section: Step 1: Training Facultymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Milestones 2.0 must be clearly articulated and reliably understood by faculty 8 . An evidence‐based methodology to foster the shared mental model, ensure high‐quality evaluations by faculty, and develop means to identify areas for improvement using learner feedback is suggested 9 . Three significant changes made to the original Milestones include updates to the content, revision of the rating system, and creation of a Supplemental Guide.…”
Section: Step 1: Training Facultymentioning
confidence: 99%
“…8 An evidence-based methodology to foster the shared mental model, ensure high-quality evaluations by faculty, and develop means to identify areas for improvement using learner feedback is suggested. 9 Three significant changes made to the original Milestones include updates to the content, revision of the rating system, and creation of a Supplemental Guide. Content updates focus on balancing the benefits of a shared mental model and developing common language around learning assessments across specialties while, most importantly, making the Milestones 2.0 specific to Geriatric Medicine trainees (Table 1).…”
Section: Step 1: Training Facultymentioning
confidence: 99%
“…Faculty development has been proposed as a way of improving rater bias, 39,40 although such interventions could still result in faculty scores that are more lenient 41 or more stringent. 42 It has been suggested that residency programs can identify a subset of faculty dedicated to learning and performance assessments, and make them responsible for the majority of resident assessments.…”
Section: Robustness and Dynamics Of Key Findingsmentioning
confidence: 99%
“…It is well known that assessment promotes improvement, and in medical education, evaluation is a fact of life [ 2 ]. Although many medical colleges have established a system for evaluating teaching quality, the reliability and validity of the final results are questioned [ 3 5 ]. What barriers prevent objective and accurate results from being obtained?…”
Section: Introductionmentioning
confidence: 99%